CIRCULAR DANCES AS A WAY TO OVERCOME CULTURAL DEVIATION (Journal of Philosophy Culture and Political Science, 2021)
Dance is a natural part of religious rituals and the main form of human communication with God, as well as the highest form of expression of inner feelings, the search for Divine Unity. In the dance, the first person accepted the planetary and cosmic rhythms and processes, showed and expressed them through movement. He comes into direct contact with the forces of nature. Dance as a symbolic form of culture is associated with magical rituals. Circular dances are known as a means of achieving collective harmony and communicating with the spirits of nature. The interpretation of movements and movements in the circular movements of nomads is perceived as an art and as a ritual dance.It is known that movement and dance were a form of the first language that existed before the advent of writing and music. At the individual and group level, humanity has experienced various internal states and signs of movement. Until the period when non-verbal language was invented, dance was an important way of transmitting the historical, cultural code from generation to generation. Circular dances are widespread in the Middle East, Eastern and Southern Europe. Modern circular dance combines traditional folk dances, mainly from European or Eastern countries, with dances that are synthesized and staged to various ancient and modern music.Keywords: circular dances, symbolic form, traditional dance, cultural deviation, nomad culture